2015
DOI: 10.1016/j.scr.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and serelaxin synergistically abrogate established airway fibrosis in an experimental model of chronic allergic airways disease

Abstract: This study determined if the anti-fibrotic drug, serelaxin (RLN), could augment human bone marrow-derived mesenchymal stem cell (MSC)-mediated reversal of airway remodeling and airway hyperresponsiveness (AHR) associated with chronic allergic airways disease (AAD/asthma). Female Balb/c mice subjected to the 9-week model of ovalbumin (OVA)-induced chronic AAD were either untreated or treated with MSCs alone, RLN alone or both combined from weeks 9-11. Changes in airway inflammation (AI), epithelial thickness, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 53 publications
5
57
1
Order By: Relevance
“…Twenty‐four hours after the establishment of chronic AAD (on d 64), subgroups of Ova‐ or Sal‐sensitized/challenged mice ( n = 8 mice/group) underwent IV or IN administration of MCA‐MSCs. In all cases, a 14‐d treatment period (from d 64 to 77) was chosen to replicate the time frame used to evaluate the intranasally delivered effects of other stem cells, such as human bone marrow–derived (stromal) MSCs (15, 28) and human amnion epithelial cells (28), in the Ova‐induced chronic model of AAD.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐four hours after the establishment of chronic AAD (on d 64), subgroups of Ova‐ or Sal‐sensitized/challenged mice ( n = 8 mice/group) underwent IV or IN administration of MCA‐MSCs. In all cases, a 14‐d treatment period (from d 64 to 77) was chosen to replicate the time frame used to evaluate the intranasally delivered effects of other stem cells, such as human bone marrow–derived (stromal) MSCs (15, 28) and human amnion epithelial cells (28), in the Ova‐induced chronic model of AAD.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…For IV administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 2 ml PBS. Mice were restrained in a Perspex restrainer (Perspex Distribution, Chelmsford, United Kingdom), and 1 × 10 6 cells/200 μl PBS were injected into the tail vein of Sal‐ or Ova‐sensitized/challenged mice, which is a commonly used cell concentration delivered to mice (13, 15, 20, 28). For IN administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 0.5 ml of PBS.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also showed efficacy of intranasal relaxin administration in allergic airway disease and cigarette smoke induced lung damage (Royce et al, 2014; Pini et al, 2016). In an exciting development, relaxin and bone marrow-derived mesenchymal stem cells or amnionic epithelial stem cells were found to be synergistic in the treatment of established airway disease (Royce et al, 2015, 2016). The mechanism for this effect is currently under investigation, but appears to be related to the matrix remodeling and anti-TGFβ effects of relaxin promoting a favorable environment for the establishment of stem cell residency in the damaged tissue (Samuel et al, 2016b).…”
Section: Relaxinmentioning
confidence: 99%